2018
DOI: 10.1093/annonc/mdx797
|View full text |Cite
|
Sign up to set email alerts
|

Clinical considerations of the role of palbociclib in the management of advanced breast cancer patients with and without visceral metastases

Abstract: BackgroundThis report assesses the efficacy and safety of palbociclib plus endocrine therapy (ET) in women with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer (ABC) with or without visceral metastases.Patients and methodsPre- and postmenopausal women with disease progression following prior ET (PALOMA-3; N = 521) and postmenopausal women untreated for ABC (PALOMA-2; N = 666) were randomized 2 : 1 to ET (fulvestrant or letrozole, respectively) plus palbocicli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 21 publications
(39 reference statements)
9
62
0
5
Order By: Relevance
“…Evidence from registrative trials confirms that palbociclib had similar had efficacy in nearly all prespecified subgroups (Finn, Crown, Ettl et al, ; Turner et al, ). Conversely, in our patient population, both ORR and CB rate were significantly higher in patients without visceral metastases.…”
Section: Discussionmentioning
confidence: 90%
“…Evidence from registrative trials confirms that palbociclib had similar had efficacy in nearly all prespecified subgroups (Finn, Crown, Ettl et al, ; Turner et al, ). Conversely, in our patient population, both ORR and CB rate were significantly higher in patients without visceral metastases.…”
Section: Discussionmentioning
confidence: 90%
“…PALOMA-3 was a prospective, randomised, multicentre, placebo-controlled study evaluating palbociclib plus fulvestrant versus placebo plus fulvestrant in patients with HRþ/HER2e MBC that had progressed on prior ET [7]. The study demonstrated improved PFS and objective response rates at predetermined time points with the combination; subgroup analyses have shown that the observed benefit was independent of menopausal status, previous ET, number of disease sites, previous lines of ET, sensitivity to previous hormonal therapy, previous chemotherapy [5,7] and presence of visceral metastases at baseline [19]. Furthermore, patients receiving the combined regimen experienced an improvement in the quality of life and a favourable toxicity profile [20e22].…”
Section: Discussionmentioning
confidence: 96%
“…For instance, in a randomized phase III clinical trial called PALOMA-3, made of 521 patients with HR-positive HER2-negative breast cancer randomly assigned to receive either palbociclib with fulvestrant or placebo with fulvestrant, the median overall survival (OS) improved by 6.9 months in the palbociclib arm versus the control arm, at a median follow-up duration of 44.8 months (HR 0.81, 95% CI 0.64-1.03, p= 0.09) 50 Although these improvements in OS were not statistically significant, they support the notion that the addition of palbociclib to fulvestrant improves mPFS by 4.9 months previously reported in 2016 51 . Moreover, the data proved that there was an even higher improvement in those patients who previously showed a sensitivity to the endocrine therapy and in those patients without visceral disease 52 . In fact, Turner et al showed that there is an improvement of 6.4 months in patients who were sensitive to endocrine therapy and had visceral disease.…”
Section: Fda-approved Cdk4/6 Inhibitors In Advanced or Metastatic Er-mentioning
confidence: 73%
“…Furthermore they also showed that there is a mPFS improvement of 9.3 months in patients without visceral disease. The mPFS was 16.6 months in patients who received palbociclib plus fulvestrant vs 7.3 months in patients who received placebo plus fulvestrant 52 .…”
Section: Fda-approved Cdk4/6 Inhibitors In Advanced or Metastatic Er-mentioning
confidence: 94%